Effects of creatine and caffeine supplementation during resistance training on body composition, strength, endurance, rating of perceived exertion and fatigue in trained young adults - Pakulak, A.; Candow, D. G.; Totosy de Zepetnek, J.; Forbes, S. C.; Basta, D. (Journal of Dietary Supplements, 2021)
The primary purpose was to determine the separate and combined effects of creatine and caffeine supplementation during resistance training on body composition and muscle performance in trained young adults. Twenty-eight participants were randomized to supplement with creatine and caffeine (CR-CAF; n = 9, 22 ± 4 years; 0.1 g·kg-1·d-1 of creatine monohydrate + 3 mg·kg-1·d-1 of caffeine anhydrous micronized powder); creatine (CR; n = 7, 22 ± 4 years, 0.1 g·kg-1·d-1 of creatine + 3 mg·kg-1·d-1 of micronized cellulose), caffeine (CAF; n = 6, 19 ± 1 years, 3 mg·kg-1·d-1 of caffeine + 0.1 g·kg-1·d-1 of maltodextrin) or placebo (PLA; n = 6, 23 ± 7 years, 0.1 g·kg-1·d-1 of maltodextrin + 3 mg·kg-1·d-1 micronized cellulose) one hour prior to performing resistance training for 6 weeks. Before and after training and supplementation, fat-free and fat mass (air-displacement plethysmography), muscle thickness (elbow and knee flexors and extensors; ultrasound), muscle strength (1-repetition maximum [1-RM] for the leg press and chest press), and endurance (one set of repetitions to volitional fatigue using 50% baseline 1-RM for leg press and chest press) were assessed. There was a group x time interaction (p = 0.049) for knee extensor muscle thickness with CR experiencing an increase over time with no changes in the other groups. There were no other between group differences for any variable. In conclusion, creatine supplementation and resistance training results in a small improvement in knee extensor muscle accretion in trained young adults.